Risk factors and outcomes of maternal obesity and excessive weight gain during pregnancy - Gaillard, Romy; Durmuş, Büşra; Hofman, Albert; Mackenbach, Johan P.; Steegers, Eric A.P.; Jaddoe, Vincent W.V. (Obesity (Silver Spring, Md.), 2013)
Objective: The prevalence of overweight and obesity among women of reproductive age is increasing. We aimed to determine risk factors and maternal, fetal and childhood consequences of maternal obesity and excessive gestational weight gain. Design and Methods: The study was embedded in a population‐based prospective cohort study among 6959 mothers and their children. The study was based in Rotterdam, The Netherlands (2001–2005). Results: Maternal lower educational level, lower household income, multiparity, and FTO risk allel were associated with an increased risk of maternal obesity, whereas maternal European ethnicity, nulliparity, higher total energy intake, and smoking during pregnancy were associated with an increased risk of excessive gestational weight gain (all p‐values <0.05). As compared to normal weight, maternal obesity was associated with increased risks of gestational hypertension (OR 6.31 (95% CI 4.30, 9.26)), preeclampsia (OR (3.61, (95% CI 2.04, 6.39)), gestational diabetes (OR 6.28 (95%CI 3.01, 13.06)), caesarean delivery (OR 1.91 (95% CI 1.46, 2.50)), delivering large size for gestational age infants (OR 2.97 (95% CI 2.16, 4.08)), and childhood obesity (OR 5.02 (95% CI:2.97, 8.45)). Weaker associations of excessive gestational weight gain with maternal, fetal and childhood outcomes were observed, with the strongest effects for first trimester weight gain. Conclusions: Our study shows that maternal obesity and excessive weight gain during pregnancy are associated with socio‐demographic, lifestyle, and genetic factors and with increased risks of adverse maternal, fetal and childhood outcomes. As compared to prepregnancy overweight and obesity, excessive gestational weight gain has a limited influence on adverse pregnancy outcomes.